Measurements of the nuclear modification factor for jets in Pb+Pb collisions at √sNN=2.76 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Dunford, Monica; Hanke, Paul; Jongmanns, Jan; Kluge, Eike-Erik; Kugel, Andreas; Lang, Valerie; Meier, Karlheinz; et al. (Physical review letters, 2015)
Measurements of inclusive jet production are performed in pp and Pb+Pb collisions at √sNN=2.76  TeV with the ATLAS detector at the LHC, corresponding to integrated luminosities of 4.0 and 0.14  nb−1, respectively. The jets are identified with the anti-kt algorithm with R=0.4, and the spectra are measured over the kinematic range of jet transverse momentum 32<pT<500  GeV and absolute rapidity |y|<2.1 and as a function of collision centrality. The nuclear modification factor RAA is evaluated, and jets are found to be suppressed by approximately a factor of 2 in central collisions compared to pp collisions. The RAA shows a slight increase with pT and no significant variation with rapidity.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A. Baas, O. Brandt, M. Dunford, P. Hanke, J. Jongmanns, E.-E. Kluge, A. Kugel, V. Lang, K. Meier, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und 2871 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 12.07.2021